Accumulation of toxic elements in an invasive crayfish species (Procambarus clarkii) and its health risk assessment to humans - Anandkumar, A.; Li, J.; Prabakaran, K.; Xi Jia, Z.; Leng, Z.; Ramasamy, Nagarajan; Du, D. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
© 2020 Elsevier Inc. The accumulation and potential health risks of eight trace elements (Cu, Cd, Cr, Mn, Zn, Pb, Hg and As) were analyzed in the commercially important crayfish and oriental river prawn species from the Zhenjiang City, Jiangsu Province, China. The accumulation sequence of elements in different tissues were as gill > walking leg > muscle. Among the analyzed elements, majority of the elements were accumulated in the gill tissue, while Hg was concentrated in abdominal muscle and Zn in walking leg tissues. The elements Zn (95.9 μg g−1) and Cd (0.02 μg g−1) were the most and the least accumulated elements in the abdominal muscle tissue. The calculated estimated daily intake (EDI) and hazard indices (HI) of the analyzed elements in the tissue organs of Procambarus clarkii and Macrobrachium nipponense species were lower than the Chinese Food Health Criterion and international guideline values and results in no acute toxicities and thus, safe for human consumption. This study also suggests that Procambarus clarkii species can be used as an effective bio-indicator organism for examining the toxic heavy metals in the freshwater ecosystems.